2018
DOI: 10.3390/ijms19061814
|View full text |Cite
|
Sign up to set email alerts
|

Yeast-Based Screen to Identify Natural Compounds with a Potential Therapeutic Effect in Hailey-Hailey Disease

Abstract: The term orthodisease defines human disorders in which the pathogenic gene has orthologs in model organism genomes. Yeasts have been instrumental for gaining insights into the molecular basis of many human disorders, particularly those resulting from impaired cellular metabolism. We and others have used yeasts as a model system to study the molecular basis of Hailey-Hailey disease (HHD), a human blistering skin disorder caused by haploinsufficiency of the gene ATP2C1 the orthologous of the yeast gene PMR1. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…CQ CL belongs to the quinoline family and it has been demonstrated that 8-hydroxyquinoline (8HQ), its precursor, can restore metal homeostasis in models of Alzheimer’s disease [ 47 ]. Furthermore, besides its antimicrobial activity nalH is also able to complex with iron and has been found to be able to reduce the sensitivity to the ROS inducing agent menadione in a yeast model of Hailey-Hailey disease [ 58 ]. On the basis of these properties, we can speculate that the mechanism that underlies their rescue ability could lie on their property to chelate the excess iron and reducing the oxidative stress and maybe the membrane damage.…”
Section: Discussionmentioning
confidence: 99%
“…CQ CL belongs to the quinoline family and it has been demonstrated that 8-hydroxyquinoline (8HQ), its precursor, can restore metal homeostasis in models of Alzheimer’s disease [ 47 ]. Furthermore, besides its antimicrobial activity nalH is also able to complex with iron and has been found to be able to reduce the sensitivity to the ROS inducing agent menadione in a yeast model of Hailey-Hailey disease [ 58 ]. On the basis of these properties, we can speculate that the mechanism that underlies their rescue ability could lie on their property to chelate the excess iron and reducing the oxidative stress and maybe the membrane damage.…”
Section: Discussionmentioning
confidence: 99%
“…An experiment in vitro showed that naringenin could significantly reduce the production of ROS in keratinocytes of PV and relieve the decline of mitochondrial membrane potential; moreover, naringenin could not only enhance the levels of total antioxidant capacity, SOD and GSH-Px, but also inhibit nucleotide-binding oligomerization domain 2-mediated NF-κB pathway to protect HaCaT cell from OS injury or apoptosis induced by PV serum [147]. In another experiment basing on the Hailey-Hailey disease (HHD, a familial benign pemphigus) model, it was found that kaempferol effectively worked on HHD model via directly reducing OS of ATP2C1 gene defective keratinocytes and restraining the sensitivity to ROS, further to restore mitochondrial function; at the same time, kaempferol could activate the Nrf2 pathway and induce the downstream target NAD(P)H: quinone oxidoreductase 1 to mitigate OS damage and protect the skin cells [148]. Recently, Cassia fistula, a herbal drug containing flavonoids, has been discovered to be an excellent remedy of wound healing in PV due to its oxidation resistance, the underlying mechanism being associated with DPPH and hydroxyl radical reduction [149].…”
Section: Flavonoids In Pemphigusmentioning
confidence: 99%
“…HHD is an autosomal dominant skin disorder in which despite the association of mutation of ATP2C1 with the disease, its in vivo role remains poorly investigated [7][8][9]. The yeast model has provided important information that can explain how in Hailey-Hailey disease loss of ATP2C1 affects human keratinocytes homeostasis [10]. In yeast, inactivation of pmr-1 leads to multiple alterations, compatible with the observed defects in Ca 2+ and Mn 2+ homeostasis.…”
Section: Introductionmentioning
confidence: 99%